Artificial perches as a nucleation technique for restoration of a riparian environment: characterization of the seed rain and of natural regeneration. - Tomazi, Aline Luiza (2010)
Riparian habitats are important to the maintenance of ecological processes and environmental services. However, a significant portion of the riparian vegetation in the Brazilian Atlantic forest has been removed in response to increasing human pressure. Therefore, the application of restoration techniques in these habitats becomes essential. In this context, a nucleation model with 18 artificial perches was evaluated for the restoration of a degraded riparian area in Gaspar, Santa Catarina, Brazil, by the characterization of the seed rain and natural regeneration. In two years we collected 21,864 seeds of 51 morphospecies, and recorded 42 colonizing species. Zoochoric seeds belonging to 15 plant families comprised 17% of the seed rain and 19.05% of the spontaneously regenerating plant species. Asteraceae and Poaceae were the most represented families. The artificial perches performed the nucleating function through the increase of zoochoric seed rain. However, possibly due to different barriers that were not evaluated in this study, part of these seeds was not recruited. We recommend the application of this technique for the attraction of dispersers in degraded areas similar to the study site.